2019
DOI: 10.3389/fneur.2019.01194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Depression and Anxiety in Essential Tremor Patients: A Cross-Sectional Study in Southwest China

Abstract: Background: Essential tremor (ET) is one of the most common movement disorders, and it has been associated with anxiety and depression, but risk factors for these mental symptoms are unclear. This study aimed to evaluate the prevalence and potential risk factors of depression and anxiety in ET patients in China.Methods: This cross-sectional study involved 245 Han Chinese patients with ET. Depression was assessed using the Hamilton Depression Rating Scale-24 Items, and anxiety was assessed using the Hamilton An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Non-motor features, particularly depression and anxiety, have been increasingly reported in patients with isolated ET [ 3 37 38 39 40 41 42 43 ]. However, other studies have not found a significant association between depression and ET [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor features, particularly depression and anxiety, have been increasingly reported in patients with isolated ET [ 3 37 38 39 40 41 42 43 ]. However, other studies have not found a significant association between depression and ET [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we explored the correlation between affective symptoms and MT, which revealed MT to be associated with anxiety and depression symptoms in ET 22 . Recently, Bologna et al 9 reported patients with head tremor to have a higher occurrence of psychiatric disorders, and Peng et al 23 showed that ET patients with head tremor had a higher incidence of memory and affective disorders than patients without head tremor.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most common movement disorders, especially in the elderlys (Louis and Ferreira, 2010;SepĂșlveda Soto and Fasano, 2020), and a potential risk factor for other neuropsychiatric conditions, such as depression and anxiety (Huang et al, 2019;Louis, 2010). The socio-economic burden inflicted by ET is insurmountable, as it negatively affects the well-being and productivity of the patients and their caregivers (Monin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%